2017
DOI: 10.1109/tnet.2017.2689019
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Network Robustness via Shielding

Abstract: Abstract-We consider shielding critical links to guarantee network connectivity under geographical and general failure models. We develop a mixed integer linear program (MILP) to obtain the minimum cost shielding to guarantee the connectivity of a single SD pair under a general failure model, and exploit geometric properties to decompose the shielding problem under a geographical failure model. We extend our MILP formulation to guarantee the connectivity of the entire network, and use Benders decomposition to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…A problem that explores the shielding of critical links to enhance the robustness of a network, in which shielded links are resilient to failures, is investigated in [8]. The problem is to find the minimum cost shielding in order to resist both independent random failures and correlated failures, such that connectivity between all source-destination pairs is always maintained.…”
Section: B Cbd For Critical Link Shieldingmentioning
confidence: 99%
See 1 more Smart Citation
“…A problem that explores the shielding of critical links to enhance the robustness of a network, in which shielded links are resilient to failures, is investigated in [8]. The problem is to find the minimum cost shielding in order to resist both independent random failures and correlated failures, such that connectivity between all source-destination pairs is always maintained.…”
Section: B Cbd For Critical Link Shieldingmentioning
confidence: 99%
“…D2D networks [12,14] iii. Wired infrastructure WANs [8] capacity restrictions). As the network size increases, the number of decision variables and constraints also increases and the computational complexity of the decision-making algorithm becomes the bottleneck.…”
mentioning
confidence: 99%
“…This is done by introducing two heuristic-based link prioritization strategies for improving network resilience: one is built upon the concept of betweenness centrality, while the other one adopts the measure that the authors named as the observed link criticality. Zhang et al [35] considered shielding critical links (e.g. strengthening cables), under general and geographical failure models.…”
Section: Enhancing the Disaster-resistance Of Existing Network mentioning
confidence: 99%
“…Moreover, 75% of all submarine fiber-optic cable faults occur in water depths shallower than 200 m, because of fishing and shipping activities [1]. These failures can be reduced by providing additional shielding at a minimum cost by employing approaches like Zhang et al [2] present. Despite the fact that failures caused by natural disasters are less than 10% of all failures (occurred both in deep and shallow water), when focusing on deep-water cables, at least 31% of submarine cable failures are prompted by natural disasters [1].…”
Section: Introductionmentioning
confidence: 99%
“…There are some recent work that focus on disaster-resilient network design and traffic engineering, but mostly they focus on impacts of disasters to terrestrial networks and cables buried under ground as in [2], [8][9][10][11][12]. Cao et al [13] investigate a disaster-resilient network design particularly in submarine environment.…”
Section: Introductionmentioning
confidence: 99%